The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/ange.200903857
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced NH3 Selective Catalytic Reduction for NOx Abatement

Abstract: Nitrogen oxides NO x , which include NO (nitrogen monoxide), NO 2 (nitrogen dioxide), and N 2 O (nitrous oxide), are currently considered to be among the most dangerous air pollutants, as they cause acid rain, contribute to photochemical smog, and have direct harmful effects on human health. For all these reasons, in the last decades NO x emissions have been regulated in industrialized countries by more and more restrictive legislation.[1] Selective catalytic reduction (SCR) technology is well established and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 11 publications
1
45
0
Order By: Relevance
“…Among them, 24 h is the optimized time period of material synthesis. The resultant Mn-24 h shows the best performance and the time durations for 100% and 60% removal of 10 ppm NO are as long as 10 h and 21 h, respectively, which is much better than that of previously reported mesoporous X-Mn materials (4 h and 5 h for 100% and 60% removal, respectively 7 ) and Co 3 Table S1, ESI †), the surface state of the synthesized Mn-t h materials determines their performances, which will be discussed below.…”
mentioning
confidence: 66%
“…Among them, 24 h is the optimized time period of material synthesis. The resultant Mn-24 h shows the best performance and the time durations for 100% and 60% removal of 10 ppm NO are as long as 10 h and 21 h, respectively, which is much better than that of previously reported mesoporous X-Mn materials (4 h and 5 h for 100% and 60% removal, respectively 7 ) and Co 3 Table S1, ESI †), the surface state of the synthesized Mn-t h materials determines their performances, which will be discussed below.…”
mentioning
confidence: 66%
“…3,4 This includes emissions from ships, diesel locomotives, or gas turbines, and of increasing importance are those from heavy-duty vehicles and passenger cars using diesel engines. 73 The ndings of this work emphasize the need for control measures for traffic emission of NH 3 , to reduce effects on aerosol mass through organic ammonium salt formation.…”
Section: Resultsmentioning
confidence: 95%
“…As shown in Figure S2, NO x conversion of Cu/bauxite is gradually enhanced when NO 2 /NO x ratio is increased from 0.25 to 0.5, and reaches the maximum at 0.5, subsequent drop of NO x conversion is observed at 0.75 and 1.0. It was reported that when NH 3 and NO 2 were fed into the reactor, NH 4 NO 3 can be formed at low temperature 113. Since NH 4 NO 3 cannot be detected directly by our apparatus, transient response method (TRM) of Cu/bauxite at 150 °C was conducted to indirectly estimate the amount of NH 4 NO 3 according to N-balance.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen oxides (NO x ) are considered as one of serious air pollutants, they are mainly emitted from automobile exhaust gas and industrial combustion of fossil fuels 123. To meet for more and more stringent regulations of NO x emission, several promising techniques including NO x storage and reduction (NSR) and selective catalytic reduction (SCR) have been proposed for NO x post-treatment 23.…”
mentioning
confidence: 99%